Functional characterization and potential therapeutic avenues for variants in the NTRK2 gene causing developmental and epileptic encephalopathies. Issue 1 (10th December 2021) - Long, Ashlee; Crouse, Andrew; Kesterson, Robert A.; Might, Matthew; Wallis, Deeann
Abstract: Variants within the Neurotrophic Tyrosine Kinase Receptor Type 2 ( NTRK2) gene have been discovered to play a role in developmental and epileptic encephalopathies, a group of debilitating conditions for which little is known about cause or treatment. Here, we determine the functional consequences of two variants: p.Tyr434Cys (Y434C) (located in the transmembrane domain) and p.Thr720Ile (T720I) (located in the catalytic domain). Wild‐type and variant cDNAs were constructed and transfected into HEK293 cells. In cell culture, variant Y434C exhibited ligand‐independent activation of tropomyosin‐related kinase B (TRKB) signaling with an associated abnormal response to brain‐derived neurotrophic factor (BDNF) stimulation and increased levels of phosphorylated extracellular signal‐regulated kinase (ERK) and ETS like‐1 protein (ELK1) activity. Expression of variant T720I resulted in decreased TRKB signaling with reduced mTor activity as determined by decreased levels of phosphorylated S6. With the deleterious mechanisms characterized, we utilized mediKanren (a novel artificial intelligence tool) to identify therapeutics to compensate for the pathological effects. Downregulation of TRKB through inhibition with mediKanren‐predicted compound 1NM‐PP1 led to decreased MEK activity. Upregulation of TRKB signaling by mediKanren‐predicted valproic acid led to subsequent increase of mTor activity. Overall, our results provide further characterization of the pathogenicity of these two variants in the NTRK2 gene. Indeed, Y434C is the first patient‐specific NTRK2 variant with demonstrated hypermorphic activity. Furthermore, we observed that variants Y434C and T720I result in distinct functional consequences that require distinct therapeutic strategies. These data suggest the possibility that unique mutations within different regions of the NTRK2 gene results in separate clinical presentations, representing distinct genetic disorders requiring unique therapeutics.